2022
DOI: 10.15441/ceem.22.318
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of direct transport to trauma centers among patients with unintentional injuries in Korea: a propensity score-matched analysis

Abstract: Objective: This study investigated the characteristics and survival rates of patients with unintentional severe trauma who visited a regional trauma center (TC) or a non-TC.Methods: This retrospective, national, population-based, observational, case-control study included patients with abnormal Revised Trauma Score from January 2018 to December 2018. We divided hospitals into two types, TC and non-TC, and compared several variables including in-hospital mortality. Propensity score matching was used to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…PSM was conducted by re-sampling in the present study to control for factors influencing survival rates. Unlike studies on unintentional injuries, 31 TC patients showed higher survival rates than non-TC patients in terms of survival after hospital admission and final survival rate after ED arrival. Although patients with intentional trauma injuries have a higher severity of injuries compared with patients with intentional trauma, 29 30 TC treatment may lead to quicker transfer to the operating room and BAE, resulting in shorter ED stays and higher survival rates.…”
Section: Discussioncontrasting
confidence: 76%
“…PSM was conducted by re-sampling in the present study to control for factors influencing survival rates. Unlike studies on unintentional injuries, 31 TC patients showed higher survival rates than non-TC patients in terms of survival after hospital admission and final survival rate after ED arrival. Although patients with intentional trauma injuries have a higher severity of injuries compared with patients with intentional trauma, 29 30 TC treatment may lead to quicker transfer to the operating room and BAE, resulting in shorter ED stays and higher survival rates.…”
Section: Discussioncontrasting
confidence: 76%
“…3 4 5 Korea’s trauma system is currently in the stage of construction, starting with the designation of regional trauma centers in 2012. The introduction of a regional trauma center reduced the mortality rate, 6 7 8 but the transfer rate between hospitals increased. 7 Regional trauma centers remain in operation, but there is no transport protocol for trauma patients in prehospital and hospital stage.…”
Section: Introductionmentioning
confidence: 99%